User acceptance testing of the ‘FurWish’ location-based mobile application: an empirical study on pet adoption and surrender services - Mazlan, Marnie Umirah; Jamaluddin, Muhammad Nabil Fikri; Abd Halim, Iman Hazwam; Ibrahim, Alif Faisal; Mohd Fuzi, Mohd Faris (UiTM Cawangan Perlis, 2025)
The increasing number of stray animals demands an effective way to connect pet owners who intend to surrender their pet with potential pet adopters. The manual approach to pet surrender and adoption often faced many challenges, such as limited outreach, communication, and options for the adopters. Unadopted pets may lead to an increasing number of stray animals and cause disturbance in residential areas. In this paper, we present a more detailed discussion on the development and evaluation of a location-aware mobile application named FurWish. The mobile application allows users to post information about their pet for listings, location-aware pet searches, setting up appointments for adoption, and notifications. The development adapted a three-phase methodology from Waterfall Model which includes requirement identification, design and development, and evaluation. Requirement identification involved reviews of literature and existing mobile apps. In the design phase the user interface design is drafted using diagrams and sketches, and the development phase involved implementation using Android Studio and Firebase with the integration of Google Location Services for displaying maps. In the evaluation phase, a user acceptance test (UAT) is conducted to test four key aspects, which are Attitude Towards Using (ATT), Behavioural Intention to Use (BI), Perceived Usefulness (PU) and Perceived Ease of Use (PEU). 33 respondents were given 12 questions after they had explored and used the functions and features of the mobile application. Results from UAT show FurWish has achieved high scores over four key aspects, with the highest score achieved under PU. This shows the user's acceptance of its effectiveness in supporting the pet adoption and surrender process while supporting animal welfare.